Routine Hematology Findings in Pulmonary Tuberculosis Cases at Regional General Hospital of Dr. Pirngadi, Medan, Indonesia - Jenny Ria Sihombing; Gabriella M.C. Sipahutar; Nathalia E.R. Sipahutar; Rotua Chatarina Simanjuntak; Suhartomi (Postgraduate, University of Mataram, 2025)
Pulmonary Tuberculosis (TB) is an infection of the lung parenchyma caused by Mycobacterium tuberculosis and is transmitted via droplets. A routine hematological examination is crucial for evaluating disease progression, complications, and therapeutic responses. Thus, this study aimed to To identify routine hematological characteristics in pulmonary tuberculosis patients in RSUD Dr. Pirngadi Kota Medan. This observational study with cross-sectional design included 105 pulmonary tuberculosis patients, that selected via total sampling technique from 2019 to 2020. Data on demographic characteristics (age, sex, and occupation) and hematological profiles were analyzed. The majority of patients were male (67.6%), aged 46–55 years (24.8%), and worked as self-employed (47.6%). Hematological profiles showed elevated neutrophils (72.4%) and erythrocyte sedimentation rate (53.3%), alongside reduced hemoglobin (58.1%), hematocrit (61%), and lymphocytes (83.8%). Most patients had normal number of leukocytes (52.4%), platelets (63.8%), monocytes (47.6%), eosinophils (87.6%), and basophils (99%). he most characteristic routine hematological changes in pulmonary tuberculosis patients include decreased hemoglobin, hematocrit, and lymphocytes, as well as increased neutrophils and erythrocyte sedimentation rate. These findings emphasize the importance of hematological examination in the diagnosis and monitoring of pulmonary tuberculosis.